Valuation of rice postharvest losses in Sub-Saharan Africa and its mitigation strategies - Ndindeng, S.A.; Candia, A.; Mapiemfu, L.D.; Rakotomalala, V.; Danbaba, N.; Kulwa, K.; Houssou, P.; Sow, M.; Jarjui, M.O.; Coulibaly, S.S.; Baidoo, A.E.; Moreira, J.; et al. (Elsevier, 2021)
Data on rice harvest and postharvest loss in Sub-Sahara Africa (SSA) is scanty making it difficult for stakeholders to appreciate the loss and set priority areas for loss reduction along the value chain. To address this problem, a protocol was developed and validated for postharvest loss (PHL) quantification in SSA. Quantitative losses at each segment were determined by field measurements. Interactive effect of origin of rice (domestic versus imported) and type of processing (white versus parboiled milled) on rice price in 33 markets in Africa was used to estimate qualitative loss for both white and parboiled milled rice. Total PHL for rice in SSA in 2018 is estimated at about US$ 10.24 billion, representing 47.63% of the expected total production. The highest loss recorded was quantitative loss before and during harvesting, followed by qualitative loss along the entire value chain, quantitative loss during milling, parboiling, threshing in that order, with the lowest being quantitative loss during drying. Priority areas to be targeted for PHL reduction in SSA and some loss mitigation tools and technologies piloted or suitable for SSA are proposed.